Insights from field applications of miscible gases based EOR for unconventional oil reservoirs: A review - Dheiaa Alfarge; Ahmed M. Aljarah; Najeh Alali (Unconventional Resources)
The oil industry has experienced notable changes due to the development of unconventional liquids rich reservoirs over the past decade. Shale oil reservoirs have become a primary focus for oil and gas investors as traditional onshore deposits have dwindled. These non-traditional reserves hold substantial original oil, but their recovery rate is less than 10 %. Utilizing miscible gas-based enhanced oil recovery (EOR) techniques, which are effective in tight oil reservoirs, has the potential to enhance oil recovery in these formations.This research conducts an analysis of the feasibility of using miscible gas-based EOR methods in shale oil reservoirs. Initially, the EOR mechanisms involving various miscible gases are introduced, including molecular diffusion, adsorption, swelling, and viscosity reduction, are summarized and explored. Subsequently, the impact of operational factors such as injection rate, cycle count, and injection duration on the efficacy of miscible gases in boosting oil recovery from unconventional oil reservoirs are examined. Moreover, the outcomes of pilot tests employing diverse miscible gas-based EOR in shale oil reservoirs are discussed. The findings reveal that molecular diffusion is the primary mechanism enhancing oil recovery in shale oil reservoirs. This mechanism positively influences the oil recovery factor through CO2 injection, while it has no effect when injecting natural gas. Adsorption, however, negatively affects well performance in CO2-EOR. Additionally, the number of huff-n-puff cycles negatively impacts CO2-EOR but benefits NGs-EOR. Overall, the performance of natural gas (NG) injection surpasses that of CO2 injection in enhancing oil recovery in field pilot tests. Moreover, the study concludes that unconventional reservoirs respond much quicker to injected natural gas compared to CO2.